Preparation method of mixed mortar

By adding specific auxiliary materials to the mixed mortar and using their components to form a gelled substance and a crosslinking network, the existing mixed mortar structure is solved and the problems of loose and insufficient strength are achieved, and higher compressive and flexural strength properties are achieved.

CN119841589AInactive Publication Date: 2025-04-18BEIJING YIHENG CONCRETE CONSTR ENG CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510066929.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The structure of existing mixed mortars is loose, resulting in insufficient strength and performance, which is difficult to meet the needs of construction operations.

Method used

By adding straw, corn cob, peanut shell and rice husk during the preparation of the mixed mortar, and using the amorphous silica and cellulose components in these auxiliary materials, a gelled substance and a crosslinking network are formed to improve the density and toughness of the mortar.

Benefits of technology

It significantly improves the compressive strength and flexural strength properties of the mixed mortar, making its structure more dense and stable, and is suitable for a wider range of architectural applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005244538660000101
    Figure BDA0005244538660000101
Patent Text Reader

Abstract

The invention relates to the technical field of mixed mortar, in particular to a preparation method of the mixed mortar, which comprises the following steps: S1, base material preparation: the base material is prepared from the following raw materials in parts by weight: 80-100 parts of mixed sand, 20-30 parts of water, 20-30 parts of cement, 10-20 parts of fly ash, 0.1-0.3 part of a water reducing agent and 0.1-0.3 part of a thickening agent, the cement is divided into a component A and a component B, and the component B is composed of a component C and a component D; the mass ratio of the component A cement to the component B cement is 8: 2. According to the invention, by utilizing the amorphous silicon dioxide component contained in the straw and the rice husk, when the mixed mortar is mixed, the amorphous silicon dioxide and calcium hydroxide in the cement are subjected to pozzolanic reaction to generate gelling substances, and the gelling substances can be filled in pores of the mixed mortar, so that the structure of the mixed mortar becomes compact; therefore, the structural strength of the mixed mortar is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of mixed mortar, and in particular to a method for preparing mixed mortar. Background Art

[0002] Mixed mortar is a building material made from a mixture of cement, lime, sand and other raw materials. It is commonly used in construction operations such as masonry, plastering, ground engineering and repair.

[0003] In the prior art, mixed mortar is usually prepared by mixing a large amount of granular powders. The granular powders have the defects of smooth surface and inability to be tightly combined, which makes the structure of the mixed mortar loose and affects the strength performance of the mixed mortar. Based on this, the present invention provides a method for preparing a mixed mortar. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a mixed mortar. The mixed mortar prepared by the present invention not only has good compressive strength performance, but also has excellent flexural strength performance, which effectively improves the use performance of the mixed mortar.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a mixed mortar, comprising the following steps:

[0007] S1: base material preparation, the base material is composed of the following raw materials in parts by weight: 80-100 parts of mixed sand, 20-30 parts of water, 20-30 parts of cement, 10-20 parts of fly ash, 0.1-0.3 parts of water reducer and 0.1-0.3 parts of thickener, wherein cement is divided into component A and component B, and the mass ratio of component A cement to component B cement is 8:2;

[0008] S2: base material preparation: the mixed sand, component A cement and fly ash are mixed to prepare the base material;

[0009] S3: preparing auxiliary materials, wherein the auxiliary materials are composed of the following raw materials in parts by weight: 2 to 4 parts of polypropylene fiber, 2 to 4 parts of straw, 1 to 3 parts of corn cobs, 1 to 3 parts of peanut shells and 1 to 3 parts of rice husks;

[0010] S4: auxiliary material preparation, the straw, corn cob, peanut shell and rice husk are pre-treated and then mixed with polypropylene fiber and component B cement to prepare auxiliary materials;

[0011] S5: preparing mixed mortar, mixing base material, auxiliary material and water to prepare mixed mortar.

[0012] Furthermore, the water reducer is selected from at least one of a naphthalene-based water reducer, a polycarboxylic acid-based water reducer, and a calcium lignin sulfonate water reducer.

[0013] Furthermore, the thickener is selected from at least one of methyl hydroxyethyl cellulose ether, hydroxypropyl methyl cellulose ether and guar gum ether.

[0014] Furthermore, the mixed sand is composed of machine-made sand and tailings sand, and the mass ratio of the machine-made sand to the tailings sand is 1:1.5.

[0015] Furthermore, the straw pretreatment method is as follows: the straw is cut into pieces with a cutting length of 1 to 3 mm, and the small pieces of straw are ground into powder with a particle size of 40 to 60 μm, thereby completing the straw pretreatment.

[0016] Furthermore, the corn cob pretreatment method is as follows: the corn cob is put into an oven, the oven is set at 160-200° C. for drying for 30-40 minutes, and after drying, it is crushed and ground into powder, the powder particle size is 30-50 μm, and the corn cob pretreatment is completed.

[0017] Furthermore, the pretreatment method of the peanut shell is: the peanut shell is placed in a treatment liquid and soaked for 2 to 4 hours, rinsed with clean water after soaking, drained, sent to an oven for drying at 160 to 200°C for 30 to 40 minutes, and crushed and ground after drying. The powder particle size is 70 to 90 μm, wherein the mass of the treatment liquid is 3 times the mass of the peanut shell, and the treatment liquid is hydrochloric acid with a hydrochloric acid concentration of 4 to 6%.

[0018] Furthermore, the rice husk pretreatment method is as follows: the rice husk is subjected to air separation to remove impurities, and then is sent to a muffle furnace, the muffle furnace is set at 500-700°C for high temperature treatment for 1-3 hours to obtain ash, the ash is ground to a powder particle size of 20-30 μm, and the rice husk pretreatment is completed.

[0019] Furthermore, the base material is prepared by the following method: the mixed sand, component A cement, and fly ash are placed in a mixer, the mixer is set at 120-160 r / min and mixed for 12-16 minutes to obtain the base material, and the auxiliary material is prepared by the following method: component B cement, polypropylene fiber, and pretreated straw, corn cobs, peanut shells, and rice husks are placed in a mixer, the mixer is set at 180-220 r / min and mixed for 20-24 minutes to obtain the base material.

[0020] Furthermore, the mixed mortar is prepared by the following method: the base material and the auxiliary materials are placed in a mixer, the mixer is set to 120-160r / min for mixing for 12-16min, then water, a water reducer and a thickener are added, and the mixer is set to 180-220r / min for mixing for 8-12min to prepare the mixed mortar.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. In the present invention, by adding straw and rice husk in the process of preparing the mixed mortar, the amorphous silicon dioxide contained in the straw and rice husk is utilized. When the mixed mortar is mixed, the amorphous silicon dioxide and the calcium hydroxide in the cement will undergo a volcanic ash reaction to generate a cementitious substance. The cementitious substance can be filled in the pores of the mixed mortar, making the structure of the mixed mortar dense, thereby improving the structural strength of the mixed mortar.

[0023] 2. In the present invention, by adding corn cobs and peanut shells, the rich cellulose in corn cobs and peanut shells can be utilized, and the fiber structure can form a cross-linked network inside the mixed mortar, thereby enhancing the toughness of the mixed mortar after molding. By adding cement in batches to the base material and the auxiliary materials for mixing and preparing them separately, most of the cement is used to prepare the base material, and a small part of the cement is mixed with the various raw materials in the auxiliary materials. The raw materials of cement and auxiliary materials can be premixed, and the cement can play a role in strengthening the dispersion of the various raw materials, thereby improving the uniformity of the distribution of the various raw materials of the auxiliary materials in the mixed mortar, thereby further improving the strength performance of the mixed mortar.

[0024] 3. In the present invention, by adding polypropylene fiber to the auxiliary materials, the polypropylene fiber can contact with the raw materials to play a role in strengthening the combination. The good flexibility and tensile strength of the polypropylene fiber are utilized to make the composition of the mixed mortar more compact, forming a more stable cross-linked structure, and further improving the strength performance of the mixed mortar. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] This embodiment provides a method for preparing a mixed mortar, comprising the following steps:

[0027] S1: base material preparation, the base material is composed of the following raw materials by weight: 80-100 parts of mixed sand, 20-30 parts of water, 20-30 parts of cement, 10-20 parts of fly ash, 0.1-0.3 parts of water reducer and 0.1-0.3 parts of thickener, wherein cement is divided into component A and component B, and the mass ratio of component A cement to component B cement is 8:2;

[0028] S2: base material preparation: mixing sand, component A cement, and fly ash to prepare the base material;

[0029] S3: preparing auxiliary materials, the auxiliary materials are composed of the following raw materials in parts by weight: 2 to 4 parts of polypropylene fiber, 2 to 4 parts of straw, 1 to 3 parts of corn cobs, 1 to 3 parts of peanut shells and 1 to 3 parts of rice husks;

[0030] S4: auxiliary material preparation, straw, corn cob, peanut shell and rice husk are pre-treated and then mixed with polypropylene fiber and component B cement to make auxiliary materials;

[0031] S5: preparing mixed mortar, mixing base material, auxiliary material and water to prepare mixed mortar.

[0032] In some embodiments, the water reducer is selected from at least one of a naphthalene-based water reducer, a polycarboxylic acid-based water reducer, and a calcium lignin sulfonate water reducer.

[0033] In some embodiments, the thickener is selected from at least one of methyl hydroxyethyl cellulose ether, hydroxypropyl methyl cellulose ether, and guar gum ether.

[0034] In some embodiments, the mixed sand is composed of machine-made sand and tailings sand, and the mass ratio of the machine-made sand to the tailings sand is 1:1.5.

[0035] In some embodiments, the straw pretreatment method is as follows: the straw is cut into pieces with a cutting length of 1 to 3 mm, and the small pieces of straw are ground into powder with a particle size of 40 to 60 μm, thereby completing the straw pretreatment.

[0036] In some embodiments, the corn cob pretreatment method is as follows: the corn cob is placed in an oven, the oven is set at 160-200°C for drying for 30-40 minutes, and after drying, the corn cob is crushed and ground into powder with a particle size of 30-50 μm to complete the corn cob pretreatment.

[0037] In some embodiments, the pretreatment method of peanut shells is: the peanut shells are placed in a treatment liquid and soaked for 2 to 4 hours, rinsed with clean water and drained, and sent to an oven for drying at 160 to 200°C for 30 to 40 minutes. After drying, they are crushed and ground into powder, and the particle size of the powder is 70 to 90 μm. The mass of the treatment liquid is 3 times the mass of the peanut shells, and hydrochloric acid is used as the treatment liquid, and the concentration of hydrochloric acid is 4 to 6%.

[0038] In some embodiments, the pretreatment method of rice husk is as follows: the rice husk is subjected to air separation to remove impurities, and then sent to a muffle furnace, the muffle furnace is set to a high temperature of 500-700°C for 1-3 hours to obtain ash, the ash is ground into powder with a particle size of 20-30 μm, and the pretreatment of the rice husk is completed.

[0039] In some embodiments, the base material is prepared by the following method: mixed sand, component A cement, and fly ash are placed in a mixer, the mixer is set to 120-160r / min and mixing is carried out for 12-16 minutes to obtain the base material, and the auxiliary material is prepared by the following method: component B cement, polypropylene fiber, and pretreated straw, corn cobs, peanut shells, and rice husks are placed in a mixer, the mixer is set to 180-220r / min and mixing is carried out for 20-24 minutes to obtain the base material.

[0040] In some embodiments, the mixed mortar is prepared by the following method: the base material and the auxiliary materials are placed in a mixer, the mixer is set to 120-160r / min for mixing for 12-16 minutes, then water, a water reducer and a thickener are added, and the mixer is set to 180-220r / min for mixing for 8-12 minutes to prepare the mixed mortar.

[0041] In this embodiment, by adding straw and rice husk during the preparation of the mixed mortar, the amorphous silicon dioxide contained in the straw and rice husk will undergo a volcanic ash reaction with the calcium hydroxide in the cement during the mixing of the mixed mortar to generate a cementitious substance. The cementitious substance can be filled in the pores of the mixed mortar to make the structure of the mixed mortar dense, thereby improving the structural strength of the mixed mortar. By adding corn cobs and peanut shells, the fiber structure can form a cross-linked network inside the mixed mortar by utilizing the rich cellulose in the corn cobs and peanut shells, thereby enhancing the toughness of the mixed mortar after molding. By adding cement in batches to the base material and the auxiliary materials separately, the mortar can be made into a mortar with a cross-linked network. A separate mixing preparation setting is used, most of the cement is used to prepare the base material, and a small part of the cement is mixed with the various raw materials in the auxiliary materials. The cement and auxiliary materials can be premixed, and the cement can enhance the dispersion of the various raw materials and improve the uniformity of the distribution of the auxiliary materials in the mixed mortar, thereby further improving the strength performance of the mixed mortar. By adding polypropylene fiber to the auxiliary material, the polypropylene fiber can contact with the various raw materials to enhance the bonding. The good flexibility and tensile resistance of the polypropylene fiber are used to make the composition of the mixed mortar more compact, forming a more stable cross-linked structure, and further improving the strength performance of the mixed mortar.

[0042] Based on the above embodiments, the following experiments were performed:

[0043] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.

[0044] Experiment 1:

[0045] S1: base material preparation, the base material is composed of the following raw materials in parts by weight: 80 parts of mixed sand, 20 parts of water, 20 parts of cement, 10 parts of fly ash, 0.1 parts of water reducer and 0.1 parts of thickener, wherein cement is divided into component A and component B, the mass ratio of component A cement to component B cement is 8:2, naphthalene water reducer is selected as water reducer, methyl hydroxyethyl cellulose ether is selected as thickener, and the mixed sand is composed of machine-made sand and tailings sand, and the mass ratio of machine-made sand to tailings sand is 1:1.5;

[0046] S2: base material preparation: mixed sand, component A cement, and fly ash are mixed to obtain the base material, and the base material is obtained by the following method: mixed sand, component A cement, and fly ash are placed in a mixer, and the mixer is set at 120r / min for 12 minutes to obtain the base material;

[0047] S3: Preparation of auxiliary materials, which are composed of the following raw materials in parts by weight: 2 parts of polypropylene fiber, 2 parts of straw, 1 part of corn cob, 1 part of peanut shell and 1 part of rice husk;

[0048] S4: auxiliary material preparation, straw, corn cob, peanut shell and rice husk are pre-treated and then mixed with polypropylene fiber and component B cement to make auxiliary materials;

[0049] The pretreatment method of straw is as follows: the straw is cut into pieces with a cutting length of 1 mm, and the small pieces of straw are ground into powder with a particle size of 40 μm to complete the pretreatment of straw. The pretreatment method of corn cobs is as follows: the corn cobs are placed in an oven and dried at 160°C for 30 minutes, and then crushed and ground into powder with a particle size of 30 μm to complete the pretreatment of corn cobs. The pretreatment method of peanut shells is as follows: the peanut shells are soaked in the treatment solution for 2 hours, rinsed with clean water after soaking, drained, placed in an oven and dried at 160°C for 30 minutes, and then crushed and ground into powder after drying. The grinding particle size is 70μm, wherein the mass of the treatment liquid is 3 times the mass of the peanut shell, the treatment liquid is hydrochloric acid, and the concentration of hydrochloric acid is 4%. The pretreatment method of rice husk is as follows: the rice husk is subjected to air separation to remove impurities, and then sent to a muffle furnace, the muffle furnace is set to 500℃ high temperature treatment for 1h, ash is obtained, the ash is ground to a powder particle size of 20μm, and the pretreatment of the rice husk is completed. The auxiliary material is prepared by the following method: B component cement, polypropylene fiber, and pretreated straw, corn cob, peanut shell, and rice husk are placed in a mixer, the mixer is set to 180r / min for mixing for 20min to obtain the base material;

[0050] S5: preparing mixed mortar, mixing base material, auxiliary material and water to prepare mixed mortar;

[0051] The mixed mortar is prepared by the following method: the base material and the auxiliary material are placed in a mixer, the mixer is set at 120 r / min for mixing for 12 minutes, then water, a water reducing agent and a thickener are added, and the mixer is set at 180 r / min for mixing for 8 minutes to prepare the mixed mortar.

[0052] Experiment 2:

[0053] S1: base material preparation, the base material is composed of the following raw materials by weight: 90 parts of mixed sand, 25 parts of water, 25 parts of cement, 15 parts of fly ash, 0.2 parts of water reducer and 0.2 parts of thickener, wherein cement is divided into component A and component B, the mass ratio of component A cement to component B cement is 8:2, polycarboxylic acid water reducer is selected as water reducer, hydroxypropyl methyl cellulose ether is selected as thickener, and the mixed sand is composed of machine-made sand and tailings sand, and the mass ratio of machine-made sand to tailings sand is 1:1.5;

[0054] S2: base material preparation: mixed sand, component A cement, and fly ash are mixed to obtain the base material, and the base material is obtained by the following method: mixed sand, component A cement, and fly ash are placed in a mixer, and the mixer is set at 140r / min for 14 minutes to obtain the base material;

[0055] S3: Preparation of auxiliary materials, which are composed of the following raw materials in parts by weight: 3 parts of polypropylene fiber, 3 parts of straw, 2 parts of corn cobs, 2 parts of peanut shells and 2 parts of rice husks;

[0056] S4: auxiliary material preparation, straw, corn cob, peanut shell and rice husk are pre-treated and then mixed with polypropylene fiber and component B cement to make auxiliary materials;

[0057] The pretreatment method of straw is as follows: the straw is cut into pieces with a cutting length of 2 mm, and the small pieces of straw are ground into powder with a particle size of 50 μm to complete the pretreatment of straw. The pretreatment method of corn cobs is as follows: the corn cobs are placed in an oven and dried at 180°C for 35 minutes, and then crushed and ground into powder with a particle size of 40 μm to complete the pretreatment of corn cobs. The pretreatment method of peanut shells is as follows: the peanut shells are soaked in the treatment solution for 3 hours, rinsed with clean water after soaking, drained, placed in an oven and dried at 180°C for 35 minutes, and then crushed and ground into powder after drying. The grinding particle size is 80μm, wherein the mass of the treatment liquid is 3 times the mass of the peanut shell, the treatment liquid is hydrochloric acid, and the concentration of hydrochloric acid is 5%. The pretreatment method of rice husk is: the rice husk is subjected to air separation to remove impurities, and then sent to a muffle furnace, the muffle furnace is set to 600℃ high temperature treatment for 2h, ash is obtained, the ash is ground to a powder particle size of 25μm, and the pretreatment of the rice husk is completed. The auxiliary material is prepared by the following method: B component cement, polypropylene fiber, and pretreated straw, corn cob, peanut shell, and rice husk are placed in a mixer, the mixer is set to 200r / min for mixing for 22min to obtain the base material;

[0058] S5: preparing mixed mortar, mixing base material, auxiliary material and water to prepare mixed mortar;

[0059] The mixed mortar is prepared by the following method: the base material and the auxiliary material are placed in a mixer, the mixer is set to 140r / min for mixing for 14 minutes, then water, a water reducing agent and a thickener are added, and the mixer is set to 200r / min for mixing for 10 minutes to prepare the mixed mortar.

[0060] Experiment 3:

[0061] S1: base material preparation, the base material is composed of the following raw materials in parts by weight: 100 parts of mixed sand, 30 parts of water, 30 parts of cement, 20 parts of fly ash, 0.3 parts of water reducer and 0.3 parts of thickener, wherein cement is divided into component A and component B, the mass ratio of component A cement to component B cement is 8:2, calcium lignin sulfonate water reducer is selected as water reducer, guar gum ether is selected as thickener, and the mixed sand is composed of machine-made sand and tailings sand, and the mass ratio of machine-made sand to tailings sand is 1:1.5;

[0062] S2: base material preparation: mixed sand, component A cement, and fly ash are mixed to obtain the base material, and the base material is obtained by the following method: mixed sand, component A cement, and fly ash are placed in a mixer, and the mixer is set to 160r / min for mixing for 16 minutes to obtain the base material;

[0063] S3: Preparation of auxiliary materials, which are composed of the following raw materials in parts by weight: 4 parts of polypropylene fiber, 4 parts of straw, 3 parts of corn cobs, 3 parts of peanut shells and 3 parts of rice husks;

[0064] S4: auxiliary material preparation, straw, corn cob, peanut shell and rice husk are pre-treated and then mixed with polypropylene fiber and component B cement to make auxiliary materials;

[0065] The pretreatment method of straw is as follows: the straw is cut into pieces with a cutting length of 3 mm, and the small pieces of straw are ground into powder with a particle size of 60 μm to complete the pretreatment of straw. The pretreatment method of corn cobs is as follows: the corn cobs are placed in an oven and dried at 200°C for 40 minutes, and then crushed and ground into powder with a particle size of 50 μm to complete the pretreatment of corn cobs. The pretreatment method of peanut shells is as follows: the peanut shells are soaked in the treatment solution for 4 hours, rinsed with clean water after soaking, drained, placed in an oven and dried at 200°C for 40 minutes, and then crushed and ground into powder after drying. The grinding particle size is 90μm, wherein the mass of the treatment liquid is 3 times the mass of the peanut shell, the treatment liquid is hydrochloric acid, and the concentration of hydrochloric acid is 6%. The pretreatment method of rice husk is: the rice husk is subjected to air separation to remove impurities, and then sent to a muffle furnace, the muffle furnace is set to 700℃ high temperature treatment for 3h to obtain ash, the ash is ground to a powder particle size of 30μm, and the pretreatment of the rice husk is completed. The auxiliary material is prepared by the following method: B component cement, polypropylene fiber, and pretreated straw, corn cob, peanut shell, and rice husk are placed in a mixer, the mixer is set at 220r / min for mixing for 24min to obtain the base material;

[0066] S5: preparing mixed mortar, mixing base material, auxiliary material and water to prepare mixed mortar;

[0067] The mixed mortar is prepared by the following method: the base material and the auxiliary material are placed in a mixer, the mixer is set to 160r / min for mixing for 16 minutes, then water, a water reducing agent and a thickener are added, and the mixer is set to 220r / min for mixing for 12 minutes to prepare the mixed mortar.

[0068] Comparative Example 1: The difference between this comparative example and Experiment 1 is that this comparative example does not contain polypropylene fiber.

[0069] Comparative Example 2: The difference between this comparative example and Experiment 1 is that this comparative example does not contain a water reducing agent and a thickener.

[0070] Comparative Example 3: The difference between this comparative example and Experiment 1 is that this comparative example does not contain auxiliary materials.

[0071] Comparative Example 4: The difference between this comparative example and Experiment 1 is that in this comparative example, an equal amount of fly ash is used to replace the auxiliary material.

[0072] Performance test: The mixed mortars prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were tested for performance, and the test data obtained are recorded in the following table:

[0073]

[0074] In the performance test, the mixed mortars prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were poured into the mold respectively, shaken evenly and then smoothed on the surface, cured at room temperature, and the compressive strength and flexural strength tests were carried out.

[0075] Among them, the 7d compressive strength of the mixed mortars prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were 29.4MPa, 29.6MPa, 28.7MPa, 19.6MPa, 19.4MPa, 16.4MPa and 15.8MPa, respectively;

[0076] The 28d compressive strengths of the mixed mortars prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were 44.6MPa, 46.3MPa, 44.5MPa, 29.1MPa, 29.6MPa, 23.5MPa and 22.1MPa, respectively;

[0077] The 7d flexural strength of the mixed mortars prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were 8.1 MPa, 8.3 MPa, 8.1 MPa, 7.3 MPa, 6.9 MPa, 5.2 MPa and 5.3 MPa, respectively;

[0078] The 28d flexural strength of the mixed mortars prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are 10.5 MPa, 10.8 MPa, 10.6 MPa, 8.5 MPa, 8.9 MPa, 8.2 MPa and 7.8 MPa, respectively.

[0079] It can be seen that the compressive strength and flexural strength of the mixed mortars prepared in Comparative Examples 1, 2, 3 and 4 are lower than those in Experiments 1, 2 and 3; this indicates that by adding straw and rice husks during the preparation of the mixed mortar and utilizing the amorphous silica components contained in the straw and rice husks, when the mixed mortar is mixed, amorphous silica and calcium hydroxide in cement will undergo a volcanic ash reaction to generate cementitious substances, which can fill the pores in the mixed mortar, making the structure of the mixed mortar dense, thereby improving the structural strength of the mixed mortar.

[0080] By comparing and analyzing the relevant data in the table, it can be seen that the mixed mortar prepared by the present invention not only has good compressive strength performance, but also has excellent flexural strength performance. This shows that the preparation method of the mixed mortar provided by the present invention has a broader market prospect and is more suitable for promotion.

[0081] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0082] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a mixed mortar, characterized in that: The following steps are involved: S1: base material preparation, the base material is composed of the following raw materials in parts by weight: 80-100 parts of mixed sand, 20-30 parts of water, 20-30 parts of cement, 10-20 parts of fly ash, 0.1-0.3 parts of water reducer and 0.1-0.3 parts of thickener, wherein cement is divided into component A and component B, and the mass ratio of component A cement to component B cement is 8:2; S2: base material preparation: the mixed sand, component A cement and fly ash are mixed to prepare the base material; S3: preparing auxiliary materials, wherein the auxiliary materials are composed of the following raw materials in parts by weight: 2 to 4 parts of polypropylene fiber, 2 to 4 parts of straw, 1 to 3 parts of corn cobs, 1 to 3 parts of peanut shells and 1 to 3 parts of rice husks; S4: auxiliary material preparation, the straw, corn cob, peanut shell and rice husk are pre-treated and then mixed with polypropylene fiber and component B cement to prepare auxiliary materials; S5: preparing mixed mortar, mixing base material, auxiliary material and water to prepare mixed mortar.

2. The method for preparing the mixed mortar according to claim 1, characterized in that: The water reducer is selected from at least one of a naphthalene-based water reducer, a polycarboxylic acid-based water reducer, and a calcium lignin sulfonate water reducer.

3. The method for preparing the mixed mortar according to claim 1, characterized in that: The thickener is selected from at least one of methyl hydroxyethyl cellulose ether, hydroxypropyl methyl cellulose ether and guar gum ether.

4. The method for preparing the mixed mortar according to claim 1, characterized in that: The mixed sand is composed of machine-made sand and tailings sand, and the mass ratio of the machine-made sand to the tailings sand is 1:1.

5.

5. The method for preparing the mixed mortar according to claim 1, characterized in that: The straw pretreatment method is as follows: the straw is cut into pieces with a cutting length of 1 to 3 mm, and the small pieces of straw are ground into powder with a particle size of 40 to 60 μm, thereby completing the straw pretreatment.

6. The method for preparing the mixed mortar according to claim 1, characterized in that: The corn cob pretreatment method is as follows: the corn cob is put into an oven, the oven is set at 160-200° C. for drying for 30-40 minutes, and after drying, it is crushed and ground into powder, the powder particle size is 30-50 μm, and the corn cob pretreatment is completed.

7. The method for preparing the mixed mortar according to claim 1, characterized in that: The pretreatment method of the peanut shell is as follows: the peanut shell is placed in a treatment liquid and soaked for 2 to 4 hours, rinsed with clean water after soaking, drained, sent to an oven for drying at 160 to 200° C. for 30 to 40 minutes, and crushed and ground after drying. The powder particle size is 70 to 90 μm, wherein the mass of the treatment liquid is 3 times the mass of the peanut shell, and hydrochloric acid is selected as the treatment liquid, and the concentration of hydrochloric acid is 4 to 6%.

8. The method for preparing the mixed mortar according to claim 1, characterized in that: The rice husk pretreatment method is as follows: the rice husk is subjected to air separation to remove impurities, and then is sent to a muffle furnace, the muffle furnace is set at 500-700° C. for high-temperature treatment for 1-3 hours to obtain ash, the ash is ground to a powder with a particle size of 20-30 μm, and the rice husk pretreatment is completed.

9. The method for preparing the mixed mortar according to claim 1, characterized in that: The base material is prepared by the following method: the mixed sand, component A cement, and fly ash are placed in a mixer, and the mixer is set to 120-160 r / min for mixing for 12-16 minutes to obtain the base material. The auxiliary material is prepared by the following method: component B cement, polypropylene fiber, and pretreated straw, corn cobs, peanut shells, and rice husks are placed in a mixer, and the mixer is set to 180-220 r / min for mixing for 20-24 minutes to obtain the base material.

10. The method for preparing the mixed mortar according to claim 1, characterized in that: The mixed mortar is prepared by the following method: the base material and the auxiliary material are placed in a mixer, the mixer is set to 120-160 r / min for mixing for 12-16 minutes, then water, a water reducing agent and a thickener are added, and the mixer is set to 180-220 r / min for mixing for 8-12 minutes to prepare the mixed mortar.

Citation Information

Patent Citations

  • Mixed sand wet mixed mortar and preparation method thereof

    CN110117173A

  • Thermal insulation type dry-mixed mortar and preparation method thereof

    CN117263606A

  • Anti-crack plastering mortar and preparation method thereof

    CN117843333A

  • Rigid waterproof mortar and preparation method thereof

    CN118894696A

  • Self-compacting concrete and preparation method thereof

    CN118993644A